Commercial tanning salons and melanoma risk. Issue 1 (1st January 2017) - Hoel, David G.
Abstract: There have been many case-control studies of melanoma and the use of indoor tanning equipment. A recent meta analysis of 8 credible studies in North America estimated an overall significant odds ratio of 1.23. Three of these 8 studies also reported separately on commercial use and home use of indoor tanning equipment. For home use the overall odds ratio was a significant 1.53 while for commercial use there was a non significant 1.05.